Participants' experiences of ketamine bladder syndrome: A qualitative study. Issue 2 (27th August 2018) - Gill, Paul; Logan, Karen; John, Bev; Reynolds, Fallon; Shaw, Chris; Madden, Kim
Abstract : The aim of this study is to explore recreational ketamine users' experiences of ketamine bladder syndrome (KBS) and related health care provision issues. KBS is an emerging condition caused by chronic, recreational ketamine use, which can result in extensive, irreparable damage to the bladder and urinary tract. However, little is yet known about how patients are personally affected by the condition, their help seeking behaviour or experiences of related health care services. A qualitative study, informed by Heideggerian hermeneutics was undertaken. Twelve participants affected by KBS were purposively recruited into the study from an National Health Service (NHS) continence service and a drug support agency in South Wales, UK. Data were collected through recorded, semi‐structured interviews and analysed using a three‐step approach. Participants were predominantly younger, poly‐drug users and typically developed KBS following prolonged, habitual ketamine use. The effects of KBS were considerable and included incontinence, haematuria, profound abdominal pain and embarrassment and were exacerbated by delays in help seeking, disjointed medical care and on‐going ketamine use, which was integral to the self‐management of KBS pain. KBS has significant impact on those affected and can result in extensive, irreversible damage to the bladder and urinary tract. The condition, and its management, is further compounded by chronic poly‐drug use, chaotic lifestyles and a range of complex, related co‐morbidities, which require a collaborative, multi‐disciplinary approach. Anderson's behavioural model of health services use provides an appropriate framework for better understanding help seeking/avoidance behaviour in this cohort, which can help inform clinical practice.